2013
DOI: 10.1021/jo402066b
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Apoptotic and Immunostimulatory Tetrahydroxanthone Dimers from the Endophytic Fungus Phomopsis longicolla

Abstract: Four tetrahydroxanthone dimers (1-4) and four biogenetically related monomers (5-8), including the new derivatives 4-6, were isolated from the endophyte Phomopsis longicolla. The absolute configurations of 2-4 were established for the first time by TDDFT electronic circular dichroism calculations, and that of phomoxanthone A (1) was revised by X-ray crystallography. Phomoxanthone A (1) showed the strongest pro-apoptotic activity when tested against a panel of human cancer cell lines, including cisplatin-resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
90
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 75 publications
4
90
0
Order By: Relevance
“…However, it was time-consuming to find the suitable conformers as well as choose the right calculation method. Sometimes, improper method could even lead to incorrect results1415.…”
mentioning
confidence: 99%
“…However, it was time-consuming to find the suitable conformers as well as choose the right calculation method. Sometimes, improper method could even lead to incorrect results1415.…”
mentioning
confidence: 99%
“…Compound 5 was identified as phomoxanthone A ( 5 , Figure 1) by comparison of its spectral data with that of the literature [16,17]; both compound 5 and phomoxanthone A had the same NMR, MS, ECD data (Figure S27, in Supplementary Materials) and specific rotation data.…”
Section: Resultsmentioning
confidence: 91%
“…Compounds 1 – 4 showed no cytotoxic activity against MDA-MB-435 breast cancer cells. It was reported that phomoxanthone A ( 5 ) has strong pro-apoptotic activity and immunostimulatory activity [17], so we did not consider its cytotoxicity assays in the study.…”
Section: Resultsmentioning
confidence: 99%
“…In the course of our ongoing research on bioactive natural products from endophytic fungi and their associated host plants [7][8][9][10], we became interested in the African rain forest tree Combretum dolichopetalum Engl. and Diels (Combretaceae), a plant which is hitherto chemically unexplored but is reported to posses hepatoprotective [11], antiulcer [12] and antidiabetic activities [13] and is used traditionally for the treatment of gastrointestinal disorders [14].…”
Section: Introductionmentioning
confidence: 99%